Reliable Drift of Diagrid Tall Buildings due to Seismic Load - Mahmoud, Sameh Lotfy; Abo-El Saad, Mohamed Naguib; Ghaleb, Ahmed Amin; Yousef, Ahmed Mahmoud (Applications of Modelling and Simulation, 2020)
Diagrid structures have become a favorable structural system because of their efficiency in resisting lateral and gravity loads. In addition, they save huge amounts of steel material in the design and construction of tall buildings. This research is concerned about the reliable drift for regular diagrid used in tall buildings and their sustainability in existence of seismic load. The main objective for lateral load resisting system is to satisfy constrained displacement and inter-story drift for tall buildings. The controlled sections process is based on the minimum amount of steel for diagrid elements to conserve specific lateral displacement and inter-story drift. Five groups of tall buildings are considered. Two groups have five models for each with various uniform angles of diagrid with the same height with a view to obtain the reliable angle for diagrid elements. The remaining three groups have six models in each group with various height-to-width aspect ratios, and uniform various diagrid inclination angles with a view to obtaining the reliable cross sections for diagrid elements based on deformation control. An empirical formula is suggested, and verified for the computation of the ratio between bending and shear deformations in existence of seismic load. The results concluded that diagrid buildings may govern by seismic load, sustainability is affected by the diagrid angle and Stiffness based design is a reliable method to control building drift based on an optimum S-Parameter.